Investigation the Existence of Corporate Income Tax Stickiness at the Micro Level - Mojtaba Golmohammadi Shuraki (Shahid Bahonar University of Kerman, 2020)
Objective: This article seeks to extend the concept of tax elasticity to corporate tax sensitivity. This issue is interpreted as corporate tax stickiness (changes in the corporate income tax to changes in the net income). In other words, in the sense of tax stickiness, the corporate income is analyzed instead of GDP, and the corporate income tax instead of government tax revenues. Theoretically, it is unlikely that the company's tax will always increase. In other words, when the company's income decreases, so does the tax. But given the stickiness of the tax, the pace of change between the two will be asymmetric. Tax policy is one of the most important factors affecting macroeconomic variables. Studying changes in tax revenue in response to variations in GDP is the key concept in this area. Based on the above argument, the main purpose of this study is to examine tax elasticity at a micro level (called tax stickiness). The rate of change in corporate income tax is compared to changes in corporate income (profit). Tax stickiness exists when the rate of tax reduction is less than the rate of profit reduction.   Method: In this study, data were collected from a sample of 284 companies listed on the Tehran Stock Exchange, TSE, in the period 2012-2019. Data were analyzed using a regression model.   Result: The results showed that there is no tax stickiness in the studied companies. Also, the effects of the variables of economic growth and capital intensity are not significant. However, financial leverage can decrease tax stickiness. In the third and fourth hypotheses, the effects of economic growth and capital intensity on tax stickiness were tested. It is argued that in the conditions of economic growth and high capital intensity, the level of investment of the companies increases, and the tax revenue from capital raises. Given that there is no capital tax in the tax structure, the lack of effects of economic growth and capital intensity on tax stickiness in the companies under study can be justified.   Conclusion: The reasons for the lack of effects of economic growth and capital intensity on tax stickiness can be attributed to government tax policies, reduction of reliance on corporate income tax in the studied years, and low attention to the capital taxation in the tax structure. On the other hand, tax stickiness can be attributed to the expertise of the TSE companies in tax planning compared to the non-TSE companies. In short, given the importance of tax revenue in the current condition of sanctions (reducing economic growth rates), it is desirable to allocate appropriate weight to capital tax in the state tax structure. The positive effects of revealing the uncertain tax situation and the motivation of managers' reward on tax avoidance, and the prominence of these features in the TSE companies compared to the non-TSE companies can be interpreted as non-stickiness of taxes. Also, in terms of the positive effects on tax avoidance, the lack of tax stickiness in the TSE companies can be attributed to the overconfidence of the managers of these companies. All these features can be the reasons for the non-sticking of income tax to the companies under study.